The correlation of energy performance and building age in UK schools. (November 2021) - Mohamed, Sara; Smith, Richard; Rodrigues, Lucelia; Omer, Siddig; Calautit, John
Abstract: In response to the climate emergency crisis, the UK became the first major economy to commit to net-zero greenhouse gas emissions by 2050. By adopting energy efficiency measures, UK schools alone could prevent the release of 625, 000 tonnes of CO2, the major emissions contributor. These improvements could also result in significant financial savings and enhanced comfort and productivity. The lack of understanding of how energy is used in schools is one of the key factors impairing the progress towards emissions reduction, and the relationship of this with building age, age-typical features and benchmarks is the knowledge gap the authors have attempted to bridge in this work through the largest known available dataset of school energy audits, which included a total of 150 schools built between 1873 and 2015 were conducted and analysed. Findings are reported in two stages: first, the energy consumption was correlated with building age, and second, age-typical features that influence energy efficiency were identified. The results showed that school buildings consume on average more than 200 kWh/m 2 /year of heating energy and more than 70 kWh/m 2 /year of electricity, approximately 35% and 70% higher, respectively than target values. Newer schools were found to consume less heating energy but more electricity than the older buildings. The conclusions discuss design, build and use factors that significantly impact the studied schools' energy use, and aim to inform more efficient building design and policymaking. Graphical abstract: Image 1 Highlights: Energy usage and indoor environment quality correlated with building construction period. 150 audits of Victorian-era, open-air, post-war, post-oil and BSF and CABE schools . Findings indicate that age-typical features influence energy efficiency. Schools consume heating energy and electricity substantially above target values. Newer schools consume less heating energy but more electricity than older buildings.